Mycoplasmal infection in a guigna (Leopardus guigna) from central Chile - Echeverry, Diana; Llanos-Soto, Sebastián; Palma, Cristina; Castillo, Linda; Casanova, Tomás; Troncoso, Ignacio; Valdés, Manuel; Castro, Fidel O.; González-Acuña, Daniel (Austral Journal of Veterinary Sciences, 2021)
Routine blood analysis indicated the presence of Mycoplasma-like bodies in a guigna (Leopardus guigna). Evidence of infection with Candidatus Mycoplasma haemominutum was found in blood samples using PCR and DNA sequencing of the 16S rRNA gene of Mycoplasma. Mycoplasma spp. are documented in cats but their role in the transmission of Mycoplasma to guigna populations requires investigation.